Aerobic exercise in severe mental illness: requirements from the perspective of sports medicine - Falkai, Peter; Schmitt, Andrea; Rosenbeiger, Christian P.; Maurus, Isabel; Hattenkofer, Lisa; Hasan, Alkomiet; Malchow, Berend; Heim-Ohmayer, Pascale; Halle, Martin; Heitkamp, Melanie (European archives of psychiatry and clinical neuroscience, 2022)
Major depression, bipolar disorder, and schizophrenia are severe mental illnesses. Despite receiving psychopharmacological and psychosocial treatments, about half of patients develop a chronic course with residual cognitive and negative symptoms and have a high risk for cardiovascular disease and reduced life expectancy. Therefore, add-on innovative treatment approaches are needed to improve outcome. Aerobic exercise interventions have been shown to improve global functioning, cognition, and negative and depressive symptoms in these patients. The basic mechanism of these exercise-related changes has been reported to be improved brain plasticity, e.g., increased volume of disease-related brain regions such as the hippocampus. The optimal type, duration, and frequency of exercise have not yet been determined and need to be addressed in supervised physical exercise studies. Because of the low physical activity levels, lack of drive related to negative and depressive symptoms, and high prevalence of cardiovascular comorbidities in patients with severe mental illness, besides aiming to improve symptoms of mental illness, exercise interventions should also aim to increase cardiorespiratory fitness, which they should comprehensively assess by direct measurements of maximal oxygen uptake. Based on the recommendations for developing cardiorespiratory fitness by the American College of Sports Medicine, 150 min moderate-intensity training per week or vigorous-intensity exercise training for 75 min per week are appropriate. Most studies have had relatively short intervention periods, so future studies should focus on long-term adherence to exercise by implementing motivational strategies supported by telemedicine and by identifying and targeting typical barriers to exercise in this patient population.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Aerobic exercise; Bipolar disorder; Cardiorespiratory fitness; Major depression; Neuroplasticity; Physical activity; Schizophrenia